Estudio del cultivo de lechuga romana (Lactuca sativa L.), sembrada mediante el sistema de NFT (Nutrient Film Technique), en la zona de Babahoyo - Flores Rivas, Cesar Iván (2015)
This research was conducted on the grounds of the Experimental Farm "San Pablo" of the Faculty of Agricultural Sciences at the Technical University of Babahoyo, located at km 7.5 of the road Montalvo Babahoyo- the province of Los Rios . The area has a tropical climate, according to the classification of Holdribge annual temperature of 24.7 ° C, precipitation of 1564.4 mm / year, relative humidity of 76% and annual heliophany 834.7 hours. Geographical coordinates 79º 32' west longitude, latitude south 01º49', with an altitude of 8 meters. The objective of this research was to evaluate the adaptability and productivity Romaine lettuce (Lactuca sativa L.) by NFT technique. The treatments studied were formed by planting distances of 10, 20 and 30 cm and doses of nutrient solution of 5 cc / l of solution A + 1 cc / for this research L of Solution B and 5 ml / L of Solution A + 2 cc / L of Solution B, using the Complete Randomized Design in factorial AXB, with 6 treatments and 4 repetitions. The comparisons of means were performed using Duncan test at 5% probability